Putnisite, SrCa4Cr83+ (CO3)8SO4(OH)16·25H2O, a new mineral from Western Australia: description and crystal structure. (February 2014) - Elliott, P.; Giester, G.; Rowe, R.; Pring, A.
Abstract: Putnisite, SrCa4 Cr8 3+ (CO7 )8 SO4 (OH)16 ·25H2 O, is a new mineral from the Polar Bear peninsula, Southern Lake Cowan, Western Australia, Australia. The mineral forms isolated pseudocubic crystals up to 0.5 mm in size in a matrix composed of quartz and a near amorphous Cr silicate. Putnisite is translucent, with a pink streak and vitreous lustre. It is brittle and shows one excellent and two good cleavages parallel to {100}, {010} and {001}. The fracture is uneven and the Mohs hardness 1½−2. The measured density is 2.20(3) g/cm3 and the calculated density based on the empirical formula is 2.23 g/cm3. Optically, putnisite is biaxial negative, with α = 1.552(3), β = 1.583(3) and γ = 1.599(3) (measured in white light). The optical orientation is uncertain and pleochroism is distinct: X pale bluish grey, Y pale purple, Z pale purple. Putnisite is orthorhombic, space group Pnma, with a = 15.351(3), b = 20.421(4) Å, c = 18.270(4) Å, V = 5727(2) Å 3 (single-crystal data), and Z = 4. The strongest five lines in the X-ray powder diffraction pattern are [d(Å)( I )( hkl )]: 13.577 (100) (011), 7.659 (80) (200), 6.667 (43) (211), 5.084 (19) (222, 230), 3.689 (16) (411). Electron microprobe analysis (EMPA) gave (wt.%): Na2 O 0.17, MgO 0.08, CaO 10.81, SrO 5.72, BaO 0.12, CuO 0.29, Cr2 O3 31.13, SO3 3.95, SiO2 0.08, Cl − 0.28, CO2calc 17.94, H2 Ocalc 30.30, O=Cl−0.06, total 100.81. The empirical formula, based on O + Cl = 69, is: Cr8.02 3+ Ca3.78 Sr1.08 Na0.11 Cu0.07 2+ Mg0.04 Ba0.02 [(SO4 )0.96 (SiO4 )0.03 ]0.99 (CO3 )7.98 (OH)16.19 Cl0.15 ·24.84H2 O. The crystal structure was determined from single-crystal X-ray diffraction data (Mo K α, CCD area detector and refined to R 1 = 5.84% for 3181 reflections with F 0 > 4σ F . Cr(OH)4 O2 octahedra link by edge-sharing to form an eight-membered ring. A 10-coordinated Sr 2+ cation lies at the centre of each ring. The rings are decorated by CO3 triangles, each of which links by corner-sharing to two Cr(OH)4 O2 octahedra. Rings are linked by Ca(H2 O)4 O4 polyhedra to form a sheet parallel to (100). Adjacent sheets are joined along [100] by corner-sharing SO4 tetrahedra. H2 O molecules occupy channels that run along [100] and interstices between slabs. Moderate to weak hydrogen bonding provides additional linkage between slabs.